Blisko ziemi. Kilka lekcji jeża - Sławek, Tadeusz (Zoophilologica. Polish Journal of Animal Studies, 2015)
Reading Jacques Derrida’s essay Che cos’è la poesia? as well as poems by Rainer Maria Rilke, Thomas Hardy, and Tadeusz Kijonka, we want to argue that the animal helps us to redefine the human subject. When pondering the fuzzy boundary between the human and the non-human, man interprets himself/herself not as a subject isolated in its sublime aspirations but, rather, as a fragile connection, delicate relation with what begs for his/her protection and care.